Ethical aspects and procedures for the publication of case reports in Brazil (Research, Society and Development, 2021)
The publication of a case report is intended to convey to others a new, relevant information, usually driven by an unusual path. It can generate a potential for changing clinical practice or hypotheses for new studies. Even if it is not research, all ethical principles that aim at the protection of the participant must be respected. This article presents the guidelines for writing case reports in accordance with the resolutions and regulations in force in Brazil, as well as their processing in the Research Ethics Committees / National Commission of Ethics in Research. Such information is timely as it guides researchers and ethics committees for research involving humans.